Epidemiological, sociodemographic, and clinical aspects of individuals with chronic skin lesions in an enterostomal therapy service (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To determine the epidemiological and clinical profile of individuals with chronic skin lesions treated at the Enterostomal therapy Outpatient Clinic between 2014 and March 2020. Method: A descriptive and retrospective study with a documentary analysis of medical records of patients with chronic skin lesions. Results: A total of 216 medical records of individuals aged between 21 and 94, of both genders, were analyzed. The majority resided in the Federal District (85%); were female (60%); had primary education (58%); did not work (73%); and had a monthly family income ranging from 280 to 840 dollars (62%). From a clinical point of view, most individuals were non-smokers and non-drinkers, with a predominance of women. The total number of lesions was similar between women and men, with a higher proportion of single lesions (71%), predominantly located in the lower limbs in both genders (78%), with venous stasis being the primary etiological cause (48%). Most individuals remained under treatment for up to six months (62%). Conclusion: The study outlined the profile of individuals treated at the service during the period, enabling an understanding of the demands and specificities of the population, the development of care strategies with the establishment of protocols, and the systematic application of care.